2023
DOI: 10.1002/adsc.202300016
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Induced Functionalization of para‐Benzoquinones: Access to Dihydroquinoxalines with a Tetrasubstituted Carbon Stereocenter

Abstract: Visible light induced activation of para‐benzoquinone, and its sequential coupling with alkynes and ortho‐phenylenediamines/ortho‐aminophenols is reported. The protocol provides a route for synthesizing value‐added quinoxaline derivatives with tetrasubstituted carbon stereocenter at room temperature in 36–75% yields. Mechanistic investigation suggests that the reaction proceeds via in‐situ generation of para‐quinone methide through direct excitation of para‐benzoquinone in blue light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…We believed that the electron-withdrawing effect of the exocyclic carbonyl group in the expected products would benefit their stability and avoid the introduction of bulky stabilizing groups ( i.e. aryl and tert -butyl 7,15 ), which may not be desired in further synthetic applications. First, a model reaction between p -benzoquinone and diphenylacetylene in acetonitrile under irradiation with blue light-emitting diodes (LEDs) showed that p -QM 1a can be obtained in 82% isolated yield (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We believed that the electron-withdrawing effect of the exocyclic carbonyl group in the expected products would benefit their stability and avoid the introduction of bulky stabilizing groups ( i.e. aryl and tert -butyl 7,15 ), which may not be desired in further synthetic applications. First, a model reaction between p -benzoquinone and diphenylacetylene in acetonitrile under irradiation with blue light-emitting diodes (LEDs) showed that p -QM 1a can be obtained in 82% isolated yield (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of cyclobutenes by [2 + 2] photocycloaddition of quinones with alkynes does not typically require any additional reagents, 7,10,15 although trifluoroacetic acid and potassium persulfate were recently reported as necessary additives for certain transformations of this type. 12 To evaluate the role of these reagents, we first attempted to perform [2 + 2] cycloadditions between such quinones and alkynes by the action of blue light alone (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations